Female with 46, XY karyotype - Jung, Eun Jung; Im, Do Hwa; Park, Yong Hee; Byun, Jung Mi; Kim, Young Nam; Jeong, Dae Hoon; Sung, Moon Su; Kim, Ki Tae; An, Hyo Jung; Jung, Soo Jin; Lee, Kyung Bok (Obstetrics & gynecology science, 2017)
Disorders of sex development (DSD) are congenital conditions characterized by atypical development of chromosomal, gonadal, and phenotypic sex. 46, XY DSD can result from disorders of testicular development or disorders of androgen synthesis/action. Prophylactic gonadectomy should be considered in patients with 46, XY DSD because of the increased risk of gonadal malignancy. We report two rare cases of 46, XY DSD, including XY pure gonadal dysgenesis and complete androgen insensitivity syndrome, who underwent a prophylactic gonadectomy.